Penerapan Metode Naïve Bayes Clasification Dalam Klasifikasi Jenis Penyakit ISPA - Yuwanda Purnamasari Pasrun (semanTIK, 2019)
ARI is the leading cause of infectious disease morbidity and mortality in the world. Nearly four million people die from ARI each year, 98% of which are caused by lower respiratory tract infections. Mortality rates are very high in infants, children and the elderly, especially in countries with low and medium per capita incomes. Likewise, ARI is one of the main causes of consultation or hospitalization in health care facilities, especially in the child care department. Lepo-Lepo is one of the health service units in the Lepo-Lepo sub-district of Kendari, which has data on patients with ARI. From the recapitulation results and medical reports of UPT Lepo-Lepo Puskesmas, ISPA is one of the diseases that is often suffered by patients in the Lepo-Lepo Puskesmas. The diagnosis results given are only in the form of positive or negative information, there is no information on the category of ARI suffered by patients including ISPaA or ISPbA so it is necessary to recognize patterns. One of the tasks of Data Mining is data classification, which is mapping (classifying) data into one or several classes that have been previously defined. From the research results obtained, from 50 data of ISPA patients tested, the results obtained using the naïve bayes method, using cross validation with 10 training data from 50 data, 96% correct and 4% wrong so that the application of the naïve bayes method in the type classification ARI can be applied ..